How to make innovation policies more effective: the challenge of considering the institutional context - Carrillo Pulido, Cristina; Rodríguez Cohard, Juan Carlos; Ortega-Aguaza, Bienvenido (My University, 2022)
The necessity to optimise the processes of design and implementation of instruments that stimulate R+D+i is a matter of urgency due to both the existing public sector budget constraints and the dubious effectiveness of much of the innovation strategies implemented. In this regard, the institutionalist theory makes it possible to identify the main factors that condition the emergence and success of innovative activities. It also considers that incentives for innovation should be designed considering the specificities of institutional environment rather than a one-size-fits-all type solution. In this context, the main aims of this article are two. On the one hand, to understand, through a bibliometric analysis, the scientific production that link institutional theory and innovation policies and, on the other hand, to highlight, through a literature review, the 1665 elements that should be considered for designing more effective innovation policies, with particular emphasis on factors related to the institutional context.
Keywords: Innovaciones tecnológicas; Innovation policies; Institutions